Documentación del sistema de gestión de calidad en la Empresa HS Mecanizados para el proceso de bujes según ISO 9001: 008 (2013)
Our country is currently undergoing a transition process, due to the free trade agreement (FTA) that was signed with the United States and that came into force in May 2012. The arrival of new products in the country makes companies start to Fix in quality management systems because it is a way to be competitive and not to leave the market. HS MECANIZADOS is a company that is dedicated to machining parts, started as a machining workshop, but over 12 years became an SME, has customers who are certified as SIEMENS MANUFACTURING, use CNC technology and machine tools, currently have a tendency to grow. To improve their competitiveness and therefore improve their profits, some deficiencies must be addressed, such as the lack of leadership in decision-making, there are no quality indicators, continuous improvement is not applied, there is no defined process, lack of belonging by employees, there are no objectives of any kind, there is no customer search plan. All this brings as a consequence a deficit of business organization, which generates a bad business image, continuous failures in the system, bad use of resources, personnel without criteria, loss of material, increase of inventories, expensive products and do not think about meet the customer's need. Keeping in mind that the client is the basis of every company, since with the beginning of the process and it is he who ends up with the result in his hands, it can be said that the company lost its focus and that is where the need for apply a quality management system such as ISO 9001: 2008, where the customer is the basis of everything. In addition, its implementation eliminates some of the causes and consequences generated by the lack of business organization in HS MECANIZADOS.To standardize these processes must document the correct way to do them, keep records of compliance and non-conformities of the system, have the appropriate profile of workers, among others. This is how the quality management system stops being isolated for the company and starts to be a philosophy.